2011
DOI: 10.1007/s11524-010-9534-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Exchange Sex and HIV Infection in High-Risk Heterosexual Men and Women

Abstract: Heterosexual partnerships involving the trade of money or goods for sex are a well-described HIV risk factor in Africa and Southeast Asia, but less research has been conducted on exchange partnerships and their impact on HIV infection in the United States. In our study, men and women were recruited from high-risk risk neighborhoods in New York City through respondent-driven sampling in 2006-2007. We examined the factors associated with having an exchange partner in the past year, the relationship between excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
58
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 41 publications
(49 reference statements)
10
58
1
Order By: Relevance
“…To our knowledge, this is one of the only U.S. studies to examine factors associated with men selling sex to women. Although women may be more likely to sell sex than men (Jenness et al, 2011), the frequency of men selling sex to women found in this study challenges the conventional perception of the gendered direction of exchange sex. Other research has found that men who have sex with both men and women are more likely to sell sex, compared to those who only have sex with men (Dyer et al, 2013;Weber et al, 2001).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…To our knowledge, this is one of the only U.S. studies to examine factors associated with men selling sex to women. Although women may be more likely to sell sex than men (Jenness et al, 2011), the frequency of men selling sex to women found in this study challenges the conventional perception of the gendered direction of exchange sex. Other research has found that men who have sex with both men and women are more likely to sell sex, compared to those who only have sex with men (Dyer et al, 2013;Weber et al, 2001).…”
Section: Discussioncontrasting
confidence: 70%
“…Exchange sex has previously been found to be associated with HIV infection among high-risk heterosexual men in NYC (Jenness et al, 2011). Those who sell sex may be incentivized to not use condoms (Jie et al, 2012) may have greater numbers of sex partners (Edwards et al, 2006), and may have more risky sex partners (Weber et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Women who engage in transactional sex may be at increased risk for STIs as well as unintended pregnancy (Jenness et al, 2011;Reuben, Serio-Chapman, Welsh, Matens, & Sherman, 2011). Having a healthcare provider was associated with a decreased odds of having unmet need for women's preventive healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…2-4 Homeless women are most often at risk of HIV infection through engagement in risky sexual behaviors with men. 5,6 Because of these behaviors and the increased likelihood of homeless women to engage in transactional sex, 7,8 adapting evidence-based interventions (EBIs) focused on HIV risk reduction among homeless women is imperative.…”
mentioning
confidence: 99%